Pembantu Rumah Tangga dalam Perspektif Hukum Ketenagakerjaan: Analisis Yuridis Normatif - Nikmah Dalimunthe; Tasya Fadilah (Pusat Riset dan Inovasi Nasional, 2025)
Domestic helpers (DWs) play a vital role in sustaining household life in urban areas, yet their legal position in the Indonesian labour system remains marginal and vulnerable, without adequate legal protection. This research aims to analyse juridically normatively the legal position of domestic workers within the framework of national labour law and identify regulatory gaps and structural barriers that hinder the protection of their basic rights. Using a literature study method and a normative juridical approach, this research examines legislation, legal doctrine, and recent scientific literature. The analysis shows that Law No. 13 Year 2003 does not recognise domestic workers as formal workers, and Permenaker No. 2 Year 2015 is non-binding, creating a legal vacuum that results in vulnerability to exploitation, discrimination, and human rights violations. The absence of special regulations such as the PPRT Bill and the non-ratification of ILO Convention No. 189 exacerbate structural injustice against domestic workers. This research concludes that the legal protection of domestic workers is very weak normatively and practically, so regulative reform is needed through the enactment of special laws and harmonisation of national laws with international human rights standards in order to create a fair, inclusive and social justice-based employment system.